Four new Palaearctic, Australian and Oriental species of Paraneseuthia Franz (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2020)
Four new species of the eutheiine genus Paraneseuthia Franz are described: P. libanica sp. n. (Lebanon), P. rugosa sp. n. (Papua New Guinea), P. olszanowskii sp. n. (Indonesia: Sumatra), and P. acehiana sp. n. (Indonesia: Sumatra). Paraneseuthia libanica is the second known Mediterranean (and western Palaearctic) species of this predominantly Australo-Oriental and Far Eastern genus. In order to verify whether this species with unusually slender and small adults truly belongs in Paraneseuthia, the male cephalic and thoracic morphological structures were studied and illustrated. No taxonomically important differences were found among west Palaearctic and previously studied sub-Himalayan, east Palaeartic and SE Asian species.